Russian Federation Financial Sector Assessment Program : Role of State in Financial Services - World Bank; International Monetary Fund (World Bank, Washington, DC, 2016)
State-owned financial institutions fall into three main groups: commercial banks, hybrid banks, and development institutions. The larger state-owned commercial banks/ groups include Sberbank, the VTB Bank group, and Gazprombank. Like private commercial banks, these institutions do not have a policy mandate and are profit maximizing, and target similar market segments. The main state hybrid bank is the Russian Agricultural Bank (RAB), which has a policy mandate to focus on agribusiness, while also engaging in broader commercial banking activities. The principal state development institution is the VEB group, which has a broad policy mandate, subject to a legal obligation not to compete with commercial credit institutions. It on-lends or directly lends to firms, but does not collect retail deposits.1 There are also several smaller state-owned banks that primarily engage in commercial activities and are owned by sub-national entities. The authorities should continue pursuing the gradual privatization of state-owned commercial banks, as economic conditions permit. There may be benefits to revisiting the role and structure of the state hybrid and development institutions, with corporate governance reforms being a priority.State-owned financial institutions should not be used to bail out struggling commercial banks. In other respects, the administration of financial subsidies appears to follow a number of good principles, although coordination could be improved. There have been many positive changes in the corporate governance of state-owned banks in recent years. reform of the current ownership structure could support the spread of good corporate governance practices. The composition and functioning of many SOB boards is an area that requires attention. Finally, SOB lending to SOEs should be conducted on an arm’s length basis and on commercial terms.